Psychological Well Being Individu Dewasa Awal yang Berolahraga Lari: Penelitian - Jasmine Cesaria; Sulis Mariyanti; Rully Afrita Harlianty (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Early adulthood is a transitional life stage characterized by various developmental demands. Failure to accomplish these developmental tasks may hinder individuals from achieving optimal psychological well-being. Running, as a form of physical activity, has been recognized for its positive contributions to both physical health and psychological well-being. This study aimed to describe the psychological well-being of early adults who engage in running. This study employed a descriptive quantitative design using a non-probability sampling method with incidental sampling. A total of 101 early adults in Indonesia who ran at least once a week participated in the study. Data were collected using the Psychological Well-Being Scale consisting of 40 valid items, with a reliability coefficient of α = 0.94. The results showed that 53.5% of the respondents had low levels of psychological well-being. Cross-tabulation analysis indicated that male respondents, those with bachelor's (S1) and master's (S2) degrees, individuals who ran more than three times per week, and those who participated in running communities tended to report higher levels of psychological well-being. However, both employed and unemployed respondents were found to have relatively low levels of psychological well-being.